Quantitative Assessment of Angiogenesis in Skin Wound Healing by Multi-Optical Imaging Techniques - Li, Lishuang; Sun, Yanan; He, Honghui; He, Gaiying; Ma, Shuhua; Yang, Weifeng; Wang, Yi (Frontiers in Physics, 2022)
The primary goal of wound healing therapy is to quickly close the wound and form healthy and functional scar tissue. As capillary system regeneration is an important condition for skin wound healing, it is important to dynamically monitor angiogenesis with multiple methods based on the 3D reconstruction of dermal microcirculation. In this study, we established a quantitative system to comprehensively evaluate angiogenesis and perfusion during wound healing. Full-thickness skin wounds were generated on the back of rats. Laser Doppler anemometer (LDA), laser speckle contrast imaging (LSCI), and medical electronic dermoscopy (MED) are used to observe the vasculature from the horizontal plane and quantify blood perfusion in wounds. We combined immunofluorescence staining and two-photon excited fluorescence microscopy (TPEF) to reconstruct 3D vessels for longitudinal quantification. These results indicated that new blood vessels around the wound grew parallel to the wound surface. The shape of the blood vessels changed from curved to straight, and the density of the surrounding vascular network gradually decreased as manifested by a decrease in the nodes and branches and the total length of the blood vessels. There were dense blood vessels that grew vertically to the wound surface in the center of the wound. This study established a real-time, non-invasive system to monitor re-epithelialization and angiogenesis and quantitatively assess blood vessels during wound healing, which facilitates the evaluation of new treatments for wound healing.